Estimation of genetic parameters and genetic change for stillbirth in Iranian Holstein cows: a comparison between linear and threshold models - Hossein-Zadeh, Navid Ghavi (MTT Agrifood Research Finland, 2011)
Data on stillbirth from the Animal Breeding Center of Iran collected from January 1990 to December 2007 and comprising 668810 Holstein calving events from 2506 herds were analyzed. Linear and threshold animal and sire models were used to estimate genetic parameters and genetic trends for stillbirth in the first, second, and third parities. Mean incidence of stillbirth decreased from first to third parities: 23.7%, 22.1%, and 21.8%, respectively. Phenotypic rates of stillbirth decreased from 1993 to 1998, for first, second and third calvings, and then increased from 1998 to 2007 for the first three parities. Direct heritability estimates of stillbirth for parities 1, 2 and 3 ranged from 2.2 to 8.7%, 0.6 to 5.1% and 0.1 to 3.8%, respectively, and maternal heritability estimates of stillbirth for parities 1, 2 and 3 ranged from 1.4 to 6.3%, 0.5 to 4.2% and 0.08 to 2.0%, respectively, using linear and threshold animal models. The threshold sire model estimates of heritabilities for stillbirth in this study were 0.021 to 0.071, while the linear sire model estimates of heritabilities for stillbirth in the current study were from 0.003 to 0.021 over the parities. There was a slightly increasing genetic trend for stillbirth rate in parities 1 and 2 over time with the analysis of linear animal and linear sire models. There was a significant decreasing genetic trend for stillbirth rate in parity 1 and 3 over time with the analysis of threshold animal and threshold sire models, but the genetic trend for stillbirth rate in parity 2 with these models of analysis was significantly positive. The low estimates of heritability obtained in this study implied that much of the improvement in stillbirth could be attained by improvement of production environment rather than genetic selection.
Keywords: Ko; dairy cow; genetic trend; linear model; stillbirth; threshold model